Profil Penulis Perjalanan Bisnis Hak Cipta Hiburan dalam Konteks Perkembangan Hak Cipta Hiburan pada Kegiatan Hatch - Kus Sudarsono (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
The journey of an entertainment IP may differ widely amongst IPs. However, there is a pattern that can be deducted from their journey. The journey starts from ideation and prototyping to licensing and partnership. The journey of an entertainment IP takes on multiple disciplines such as arts, marketing, business, public relation, partnership, and many more disciplines. Each stage provides its challenges to continue the journey. Further, each stage must be mastered and well-designed by the IP owner. The stages are Value Propositions, Business Model Generation, Media selection and IP Protection, Monetizing and expanding media, Collaboration and Market expansion, Partnership, and Licensing. Hatch is a mentorship event for new content creator to expand their IP, conducted by Katapel.id.